2015
DOI: 10.1515/ersc-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response, inflammation, oscillators, and disease: a systems biology approach

Abstract: Non-communicable diseases (NCDs) such as cardiovascular disease, cancers, diabetes and obesity are responsible for about two thirds of mortality worldwide, and all of these ailments share a common low-intensity systemic chronic inflammation, endoplasmic reticulum stress (ER stress), and the ensuing Unfolded Protein Response (UPR). These adaptive mechanisms are also responsible for significant metabolic changes that feedback with the central clock of the suprachiasmatic nucleus (SCN) of the hypothalamus, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 170 publications
(228 reference statements)
0
5
0
Order By: Relevance
“…The subsequent experiments revealed that the expression levels of ERS-related genes, such as GRP78, IRE1, p50ATF6 and CHOP, were increased in cells treated with TM + H 2 O 2, compared with cells treated with H 2 O 2 alone. It is well known that in the absence of ERS, the N-terminus of IRE1, p50ATF6 and PERK binds to the chaperone Grp78/Bip and they are present in inactive state ( 6 , 11 ). When ERS occurs, a large number of unfolded proteins accumulate in the ER cavity, IRE1, p50ATF6 and PERK are then separated from Grp78/Bip, and Grp78/Bip binds to the unfolded proteins ( 11 , 14 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent experiments revealed that the expression levels of ERS-related genes, such as GRP78, IRE1, p50ATF6 and CHOP, were increased in cells treated with TM + H 2 O 2, compared with cells treated with H 2 O 2 alone. It is well known that in the absence of ERS, the N-terminus of IRE1, p50ATF6 and PERK binds to the chaperone Grp78/Bip and they are present in inactive state ( 6 , 11 ). When ERS occurs, a large number of unfolded proteins accumulate in the ER cavity, IRE1, p50ATF6 and PERK are then separated from Grp78/Bip, and Grp78/Bip binds to the unfolded proteins ( 11 , 14 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the ER homeostastic balance is disrupted by a variety of physiological and pathological factors, ER stress (ERS) can be induced in the ER with increased amounts of unfolded and misfolded proteins being formed, calcium depletion and disorder of lipid synthesis ( 5 , 6 ). ERS involves three pathways, namely the unfolded protein response (UPR), Ca 2+ signaling and ER-related degradation ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ER is an important organelle for protein synthesis, folding, and modification and for calcium storage and lipid synthesis [12]. Many physiological and pathological factors, including inflammation, hypoxia, glucose deficiency, environmental toxins, viral infection, changes in Ca 2+ levels, and oxidative stress, destroy the homeostasis of ER and lead to ER dysfunction [13,14]. Dysfunction in the ER can increase the production of the misfolded or unfolded proteins in ER that can induce ER stress and trigger the unfolded protein response (UPR) [15,16].…”
Section: Overview Of Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…The NLRP3 inflammasome is the most known inflammasome. It is a multiprotein citoplasmic complex activated by pathogen-associated molecular patterns (PAMPs) (such as bacterial and viral nucleic acid), damage-associated molecular patterns (DAMPs) (for example, ATP and uric acid crystals) or environmental irritans [1][2][3].…”
Section: Short Communicationmentioning
confidence: 99%